RAZLIKE MORFOLOŠKIH OBILJEŽJA I MOTORIČKIH SPOSOBNOSTI TRANSFORMACIONIM TRETMANOM U DODATNOJ NASTAVI - Muhedin Hodžić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
This research has been carried out with a test sample group of 26o students attending The Technical School Zenica and being, at the same time, the members of the boy-scout organisation "GREEN VALLEY". The boys are at the age of 14 to 16, Bosnian and Herzegovina citizens, clinically and psychically healthy without any chracteristic morphological or locomotive damages, by chance selected and devided into two numerically equal groups, i.e.an experimental and controlling one. The controlling group have worked under the existing high school curiculum, two lessons a week, with their teachers of sports. The experimental group have also worked under the existing high school curiculum of two lessons a week, plus additional two lessons a week as planned after school activities (athletics, hand ball, basketball, volley-ball and football); they've also participated in a preparing part of the additional lessons and specifically chosen exercises in gym for body shaping, under supervision of their teachers of sports. The experimental group have also had one-day walking tour to the holiday resort Smetovi, 8500 metres away from the school building. Factorial structure in initial tests directs us to the conclusion that it concernes not an optimized configuration of locomotion because of: - the first cannonic factor being defined by the whole complex of subcutaneous fat tissue variables, while in motoric space it is defined by literally all variables of the counter omen. It clearly shows that fat tissue is a limiting factor of any moving relation. - the second cannonic factor having an unfavourable position of mass volume in relation to frequency and explosiveness, which represents a clear bio-mechanical situation; - the third cannonic factor representing description of the unfavourable mass volume composite at realization of coordinatingly saturated movements; - the fourth cannonical factor is most probably the artefact which has derived from all lacks of coordination in locomotion, being conditioned by an unfavourable complex responsable for inadequate accuracy and coordination.